The complete mitogenome of Hong Kong paradise fish (Macropodus hongkongensis), an endemic freshwater fish in South China - Liu, Hongyi (Mitochondrial DNA B Resour, 2019)
The first complete mitogenome of Hong Kong paradise fish (Macropodus hongkongensis) was determined in this study. The assembled mitogenome is 16,494 bp and consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs, and a control region. Nucleotide composition of the complete mitogenome is 30.6% A, 24.8% C, 14.8% G, and 29.8% T, with an A + T bias of 60.4%. The maximum-likelihood tree based on 13 protein-coding genes showed that M. erythropterus was the closest related species to M. hongkongensis.